Language as prayer in Finnegans Wake - Jaurretche, Colleen (Florida James Joyce series., 2020)
"This innovative analysis shows how James Joyce uses the language of prayer to grapple with intangible things in his dreamlike masterpiece Finnegans Wake. Colleen Jaurretche moves beyond what scholars know about how Joyce wrote this work to suggest exactly why it follows the order it does in its finished form"--